Strengthening Creative Economy Digital In Ambon City - Jolyne Myrell Parera; Simon Pieter Soegijono; Margaretha Rosalyn Apituley; Beatrix Adonia Talakua; Robby Djefry Lakatua (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
A creative Economy is a concept in the new economic era, which relies on information and creativity, ideas, and a stock of knowledge from human resources and is the main production factor in economic activity. Anticipating the challenges of globalized creative economy competition, a number of strategies need to be prepared, including strengthening digital infrastructure and digital talent of human resources. Ambon, the capital of Maluku Province, has only 1,304 entrepreneurs using the internet, and 34,833 out of 36,137 entrepreneurs do not use it. This phenomenon illustrates that most entrepreneurs running their businesses are still conventional or do not use digital platforms. Using qualitative research methods, and SWOT analysis, the results of this study illustrate that the strategies that can be expected from the Regional Government are: (1) strengthening digital infrastructure, (2) improving the quality of human resources in order to adapt through literacy movements, (3) strengthening the innovation ecosystem with collaboration between the Government, entrepreneurs, universities, (4) guaranteeing ease of doing business, and (5) assistance and supervision to the entrepreneurs.